Virulence and Antimicrobial Resistance in Campylobacter spp. from a Peruvian Pediatric Cohort. (9th October 2017) - Lluque, Angela; Riveros, Maribel; Prada, Ana; Ochoa, Theresa J.; Ruiz, Joaquim
Abstract : The presence of virulence factors (VFs) and mechanisms of quinolones and macrolide resistance was analyzed in Campylobacter spp. from a pediatric cohort study in Lima. In 149 isolates (39 Campylobacter jejuni and 24 Campylobacter coli from diarrheic cases; 57 C. jejuni and 29 C. coli from controls), the presence of the cdtABC and cadF genes and iam marker was established. Nalidixic acid, ciprofloxacin, erythromycin, and azithromycin susceptibilities were established in 115 isolates and tetracycline-susceptibility was established in 100 isolates. The presence of mutations in the gyrA, parC, and 23S rRNA genes was determined. The cadF gene and all genes from the cdtABC operon were significantly more frequent among C. jejuni (P < 0.0001 ); the iam marker was more frequent in C. coli (P < 0.0001 ). No differences were observed in VFs between cases and controls. Almost all isolates were tetracycline-resistant; nalidixic acid and ciprofloxacin resistance reached levels of 90.4% and 88.7%, respectively. Resistance to macrolides was 13% ( C. jejuni 4.3%; C. coli 26.1%). Resistance to ciprofloxacin was related to GyrA Thr86 substitutions, while 13 of 15 macrolide-resistant isolates possessed a 23S rRNA mutation (A2075G). Differences in the presence of VFs and alarming levels of resistance to tested antimicrobial agents were observed among C. jejuni and C. coli .